Partially hidden policy multi-authority CP-ABE scheme with constant length ciphertext - LIU Yilong; XU Shengwei; YUE Ziyan (Tongxin xuebao)
To solve the problems of low security and high resource overhead of existing hidden policy ciphertext policy attribute-based encryption (CP-ABE) schemes, a partially hidden policy multi-authority CP-ABE scheme with constant length ciphertext was proposed. Firstly, the values of the attributes in the access policy were hidden, enabling the proposed scheme to reduce the risk of private data leakage. Secondly, by fixing the ciphertext length and using outsourcing decryption techniques, the resource overhead for the user was reduced in the proposed scheme. Finally, the multi-authority management mechanism was used so that the proposed scheme avoided the key escrow problem that can easily arise when using a single authoritative authority. The security analysis proves that the proposed scheme satisfies the indistinguishability under chosen plaintext attack in the standard model, as well as the scheme’s hidden access policy and the generated outsourcing key can resist attribute value guessing attack. The overall resource overhead of the proposed scheme is proven to be lower by comparing its performance with the existing schemes.